PENERAPAN METODE LATIHAN SIAP UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS I SD NEGERI 006 TERPADU KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Hairani, Lamra (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Background action research (PTK) is the low ability to solve arithmetic operations first-class students 006 Terpadu SD Negeri Kubang Jaya, Kecamatan Siak Hulu. In addressing the problem of learning is done by applying the method of Exercise Ready. The problems in this study is whether the application is ready for training method can improve student learning outcomes Math 006 class I SD Negeri Kubang Jaya Kecamatan Terpadu Siak Hulu ?. The purpose of this research is to improve the learning outcomes of students of class I Math 006 Terpadu SD Negeri Kubang Jaya Kecamatan Siak Hulu by way of application of the method of Exercise Ready. The result of this action research is the application of methods of exercise are ready to improve learning outcomes of students in 1st grade Math 006 Terpadu Negeri Kubang Jaya Kecamatan Siak Hulu. Learning outcomes has increased from an average value was 42.25 with a category quite well, increased in the first cycle to 62.50 with both categories, and the second cycle increased to 81.50 with very good category. Before the act is done, students who pass the study only 13 students or 32.50%, this number has increased in the first cycle to 22 students or 55.00%, in the second cycle to 37 students or 92.50%. Based on observations, the writer and first grade students of SD Negeri 006 Terpadu SD Negeri Kubang Jaya Kecamatan Siak Hulu seem to understand the methods of training are ready and they can work together in learning. The use of ready training methods successfully overcome the problem of low improve mathematics learning outcomes in grade I SD Negeri 006 Terpadu SD Negeri Kubang Jaya Kecamatan Siak Hulu on the second cycle.